Perception towards sustainability polytechnic campus in Malaysia - Kasim, Zanariah; Ujang, Norsidah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2014)
The higher learning institutions in Malaysia are currently in the stage of integrating sustainable components in the campus planning and management. In the case of campuses that are located within a fast growing urban context and threatened by uncontrolled physical and social development, it is very important to ensure the sustainability of the campus environment. Due to the piecemeal planning, buildings are isolated and the public spaces are illegible. As a result, the campus environment is found to be less responsive, environmentally and socially. The aim of this study is to examine the aspects of green and eco-nature based on the users’ perception that influence the environmental and social sustainability of polytechnic campuses in Malaysia. Questionnaire surveys were conducted on 300 polytechnic communities from two premier polytechnics to identify their perceptions towards the institution in the context of sustainability. It is discovered that comfort, health, green and safety are highlighted as the most important components of sustainable campus environment. The survey results indicate that polytechnic communities in Malaysia are strongly concerned with the recreational needs and the functional use of the spaces. The need is to provide learning and working environment that support the well-being of the campus community. The findings of this study are useful reference for planners, architects, urban designers and Department of Polytechnic, Ministry of Higher Education in their effort to create a sustainable polytechnic campus. This will be in line with the aim of the polytechnics Transformation Plan 2010 to transform polytechnics into a preferred institution for higher learning.